Hospital Variation in Rates of Acid-Reducing Medication Use after Laparoscopic Sleeve Gastrectomy - Pradarelli, Jason C. (Surg Obes Relat Dis, 2015)
BACKGROUND: Postoperative gastroesophageal reflux is one of the most important long-term complications of sleeve gastrectomy, the most common bariatric procedure. OBJECTIVE: To assess variation in hospital performance with laparoscopic sleeve gastrectomy using rates of acid-reducing medication use at postoperative 1 year. SETTING: Clinical registry of bariatric surgical patients at academic and community hospitals in Michigan. METHODS: We studied 2,923 patients who underwent laparoscopic sleeve gastrectomy across 39 hospitals in the Michigan Bariatric Surgery Collaborative, 2007–2014. We compared risk- and reliability-adjusted rates of new-onset reflux—defined by new use of acid-reducing medication—across hospitals and in relation to surgical quality indicators (hospital procedure volume and 30-day complications). RESULTS: Overall, 20% of patients were newly taking acid-reducing medication at postoperative 1 year. Hospital rates of new medication use varied three-fold, ranging from 10% (95% CI, 7–15%) to 31% (95% CI, 23–40%) of patients. Of the 2 hospitals with significantly lower rates of new medication use, 1 was high-volume and 1 was medium-volume. The 1 hospital with significantly higher rates was medium-volume. Rates of acid-reducing medication use did not correlate with hospital volume or perioperative complications. CONCLUSIONS: Across Michigan hospitals, rates of new acid-reducing medication use at 1 year after laparoscopic sleeve gastrectomy varied widely and did not correlate with traditional quality indicators. Future research could explore differences in surgical technique to better understand the factors underlying variation in long-term outcomes after sleeve gastrectomy.